Giraffe : Biology, Behaviour and Conservation / [electronic resource] - Dagg, Anne Innis (Cambridge : Cambridge University Press, 2014)
With its iconic appearance and historic popular appeal, the giraffe is the world's tallest living terrestrial animal and the largest ruminant. Recent years have seen much-needed new research undertaken to improve our understanding of this unique animal. Drawing together the latest research into one resource, this is a detailed exploration of current knowledge on the biology, behaviour and conservation needs of giraffe. Dagg highlights striking new data, covering topics such as species classification, the role of infrasound in communication, biological responses to external temperature changes and motherly behaviour and grief. The book discusses research into behaviour alongside practical information on captive giraffe, including diet, stereotypical behaviour, ailments and parasites, covering both problems and potential solutions associated with zoo giraffe. With giraffe becoming endangered species in Africa, the book ultimately focuses on efforts to halt population decline and the outlook for conservation measures.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Giraffe